Abnormal mortalities of the carpet shell clam Ruditapes decussatus (Linnaeus 1756) in natural bed populations: a practical approach. Issue 8 (24th December 2012) - Aranguren, Raquel; Gomez‐León, Javier; Balseiro, Pablo; Costa, Maria M.; Novoa, Beatriz; Figueras, Antonio
Abstract In situ controlled systems based on PVC cages surrounded by a net mesh and buried in sand were designed to determine the causes of important mortalities in producing locations of carpet shell clam, Ruditapes decussatus, in two important production areas of Galicia (NW Spain). The pathogenic status of the clam populations (focusing mainly on Perkinsus sp. and clam haplosporidian) as well as changes in water temperature and salinity were recorded. Sampling was conducted during a short period of time when high mortalities were present in the two locations and in a 1‐year study when no important mortalities were registered. We found that the environmental conditions and not the presence of pathogens seemed to be related to mortalities in the study. Our results suggest that mortality rates, especially in natural beds, can emerge from a complex synergy of different factors. Moreover, we propose in situ controlled systems based on PVC cages as a useful method to control infaunal bivalve mortalities in natural beds.